The efficacy of teaching modules in enhancing students' sense of physics: Newton's laws - Annisa Maya Sari; Endang Purwaningsih; Khusaini Khusaini (Universitas PGRI Kanjuruhan Malang, 2024)
Sensemaking plays a crucial role as a bridge for students' understanding and intuition with explanations, thus addressing knowledge gaps. This bridging function helps students build new knowledge and comprehend related content materials. However, when facing physics problems, most students tend to engage in